INNOVATIVE-METHODOLOGICAL AND ORGANIZATIONAL-PEDAGOGICAL PROSPECTS FOR ACTIVATING SOCIAL ACTIVITY OF THE FUTURE TEACHERS - Sobirova Aziza Boymuradovna (Galaxy International Interdisciplinary Research Journal, 2021)
To develop students’ 21st century skills and render education more responsive to the challenges of a knowledge-based society, teachers’ development has been constantly called for. The conception of teaching as a life-long learning process is gaining momentum with the variety of conferences, courses/programmes, and published materials supporting it. But, to develop as teachers we need to understand the nature of this development. Does it mean professional, personal or social development? This article aims to clarify the meaning of teacher development through explaining what teacher professional, personal and social development mean and how these relate to teacher development.